Model atmosphere of HD101065 with individualized abundances - Khan, S. A.; Shulyak, D. V. (Одеські астрономічні публікації, 2017)
We have calculated the model atmosphere of extremely peculiar roAp star HD101065. The line opacity with individualized abundances has been executed by "line-by-line" method. Due to lack of data for the REE lines we scaled D.R.E.A.M. data base by ten. The synthetic spectrum and indices in photometric system uvby have been calculated as: b-y = 0.713, m1 = 0.336, c1 = ?0.121. We had obtained good agreement between an observation and modelling. <!--[if !supportLineBreakNewLine]--> <!--[endif]-->